The Death of Alexander the Great : What--or Who--Really Killed the Young Conqueror of the Known World? - Doherty, Paul (New York Carroll & Graf Publishers, 2004)
In May 323 BC Alexander of Macedon fell ill at Babylon; ten days later he was dead. Aged only 33 at the time of his death, Alexander had nonetheless shaken the pillars of the known world during the previous decade. In 334-33 this military genius from a small and unimpressive kingdom to the north west of Greece had raged like a wolf through the Persian Empire, conquering the lands of the Middle East, Egypt
Include Index and Reference
Keywords: Greece -- Generals -- Kings and rulers